Criminal Enforcement against Illegal Cosmetic Business Actors - Elfira S Yusuf (Universitas Negeri Gorontalo, 2020)
This study aimed to find out the Criminal Enforcement Against Illegal Cosmetic Business Actors in Gorontalo City. This type of research was empirical legal research, namely research by taking and using existing data in the field (primary) as the main data source, such as the results of interviews and observations. The Food and Drug Supervisory Agency (BPOM) should be even more assertive in providing a deterrent effect to mischievous business actors and must always carry out routine operations (surprise inspection) on business actors, not only through reports from the public and then officers going down to the field to carry out operations but must indeed be scheduled in a week how many times to do operations. If BPOM only waits for reports from the public, there will be no deterrent effect on mischievous business actors who have never been caught in raids/operations by the Food and Drug Supervisory Agency (BPOM).